Winding Characteristics and Signal Characterization of Roller During Threshing of Mature Rice - Kexin Que; Xiaobo Zhuang; Yanyun Shi; Zhexuan Ding; Zhong Tang; Tiantian Jing; Yunlong Cao; Bangzhui Wang; Yao Yu (Agriculture)
As rice yield rises, the issue of broken axis windings in mature rice threshing drums is becoming increasingly severe. To disclose the winding characteristics and signal traits of the drums during the threshing process of mature rice, this paper undertakes an analysis of the winding characteristics and signals of the drums in rice with the assistance of a vibration test and analysis system. Since rice can lead to drum winding and shaft breakage, this paper alters the driving mode of the drums to exhibit the influence of rice on them. Firstly, the transfer characteristics of the frame need to be studied and analyzed, followed by subsequent research. The test results indicate that the horizontal displacement of the cylinder axial trajectory rises with the growth of the transmission chain, while the vertical displacement drops with the growth of the transmission chain. Additionally, to investigate the effect of mature rice on the threshing performance of horizontal axis II and horizontal axis III, a control variable method was employed. This approach allowed for the observation of how mature rice influences the threshing roller by systematically adjusting both the threshing gap and the rotational speed of the roller. It can be discerned from the test results that with the reduction of the threshing gap of affected mature rice, the unstripped rate gradually declines, while the entrainment loss rate gradually increases. As the rotational speed of horizontal shaft roller III increases, the rate of uncleared material gradually decreases, while the rate of entrainment loss progressively rises. The research findings can furnish a reference for the winding characteristics of rice on rollers and the enhancement of vehicle driving comfort.